sin25π/6+cos10π/3+tan(-25π/4)+sin(-7π/3)×cos(-13π/6)=

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/28 07:28:28
sin25π/6+cos10π/3+tan(-25π/4)+sin(-7π/3)×cos(-13π/6)=
xő 0EWҖu2C$%Pф0@Z*ʴl2@;d * [dE[u-ffMF6Pǁ2 y]o۪ ^:z=ưNJM=Bto'&Ѐ }09G:7u?]ndzC,C9m:&۵uS_=m

sin25π/6+cos10π/3+tan(-25π/4)+sin(-7π/3)×cos(-13π/6)=
sin25π/6+cos10π/3+tan(-25π/4)+sin(-7π/3)×cos(-13π/6)=

sin25π/6+cos10π/3+tan(-25π/4)+sin(-7π/3)×cos(-13π/6)=
sin25π/6+cos10π/3+tan(-25π/4)+sin(-7π/3)×cos(-13π/6)
=sin(4π+ π/6)+cos(4π - 2π/3)+tan(-6π- π/4)+sin(-2π - π/3)×cos(-2π - π/6)
=sin(π/6)+cos(2π/3) + tan(-π/4) + sin(- π/3)×cos(- π/6)
=sin(π/6)-cos(π/3) - tan(π/4) - sin(π/3)×cos(π/6)
=1/2 - 1/2 - 1 - (根号3)/2 × (根号3)/2
=-1 - 3/4
=-7/4